Modeling the Performance of Faulty Linear Wireless Sensor Networks. (16th July 2014) - Mohamed, Nader; Al-Jaroodi, Jameela; Jawhar, Imad
Abstract : Wireless sensor networks (WSNs) are used to monitor long linear structures such as pipelines, rivers, railroads, international borders, and high power transmission cables. In this case, a special type of WSN called linear wireless sensor network (LSN) is used. One of the main challenges of using LSNs is the reliability of the connections across the nodes. Faults in a few contiguous nodes may cause the creation of holes (segments where nodes on either end of them cannot reach each other) which will result in dividing the network into multiple disconnected segments. As a result, sensor nodes that are located between holes may not be able to deliver their sensed information which negatively affects the network's sensing coverage. In this paper, we provide an analysis of the different types of node faults in uniformly deployed LSNs and study their negative impact on the sensing coverage. We develop an analytical model to estimate the sensing coverage in uniformly deployed sensors LSNs in the presence of node faults. We verify the correctness of the developed model by conducting a number of simulation experiments to compare both calculated and simulated results under different network configurations and fault scenarios. In addition, we use this model to demonstrate three design applications that meet with specific performance requirements.